Severe ARDS Complicated by Active Pulmonary Tuberculosis and Recurrent Nosocomial Infections: Therapeutic Challenges and Clinical Outcomes - Wei-Hung Chang; Yi-Ting Wang; Ting-Yu Hu; Li-Kuo Kuo (Life)
Background: Acute respiratory distress syndrome (ARDS) secondary to tuberculosis (TB) is rare and associated with high mortality. Management is further complicated by comorbidities and ICU-related complications. Methods: We report a 43-year-old woman with post-polio sequelae and uncontrolled diabetes who developed ARDS due to pulmonary TB, complicated by recurrent nosocomial infections and gastrointestinal bleeding. Early bronchoscopy and GeneXpert MTB/RIF PCR were performed on ICU Day 2, enabling anti-TB therapy initiation by ICU Day 3. The patient received lung-protective ventilation, prone positioning, tailored antibiotics, and multidisciplinary care. Results: The patient’s clinical course was complicated by two episodes of ventilator-associated pneumonia and gastrointestinal bleeding, but with individualized management, she achieved ventilator weaning and functional recovery. Conclusions: Early TB recognition in ARDS is crucial. Multidisciplinary ICU management, including prudent steroid use, improves outcomes.